Executive Gender Pay Gaps: The Roles of Female Risk Aversion and Board Representation1. (3rd January 2017) - Carter, Mary Ellen; Franco, Francesca; Gine, Mireia
Abstract: Using a large sample of executives in S&P 1500 firms over 1996–2010, we document significant salary and total compensation gaps between female and male executives and explore two possible explanations for the gaps. We find support for greater female risk aversion as one contributing factor. Female executives hold significantly lower equity incentives and demand larger salary premiums for bearing a given level of compensation risk. These results suggest that females' risk aversion contributes to the observed lower pay levels through its effect on ex ante compensation structures. We also find evidence that the lack of gender diversity on corporate boards affects the size of the gaps. In firms with a higher proportion of female directors on the board, the gaps in salary and total pay levels are lower. Together, these findings suggest that female higher risk aversion may act as a barrier to full pay convergence, despite the mitigating effect from greater gender diversity on the board.